الدرس النفسي لأبي نواس ما بين العقاد والنويهي (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يتطرق هذا البحث لواحـد من المناهـج العديدة التي طُبِّقَتْ في درس أبي نواس، وهو المنهج النفسـي الذي يقوم على الغوص في نفسـية الأديب ومحاولة تبيُّن أسـرارها ما دامت تشكل جزءاً من النفس الإنسانية التي اهتم بتحليلها علم النفـس. وبصورة أكثر تحديداً، تمت ضمن هذا البحث المقارنة ما بين دراستين نفسيتين قد قام بهما كل من العقـاد والنويهـي، وذلك بناءً على عقدتين اثنتين: أولهما بناءً على عقدة النرجسية التي تقوم على حب الإنسان لذاتـه، وإيثارها على ذوات الآخرين، والثاني بناء على عقدة أوديب التي تقوم على تعلق الابن بأمه وحب اسـتئثاره بها. وقد حاول كل من الناقدين أن يتتبع العقدة التي اكتشفها فيما تعدد من الميادين التي طرقها الشاعر، كحب الخمرة والحب المثلي وحب المرأة. This research deals with one of several methods which were applied in studying Abu Nuwas as a poet. It is a psychological method that depends on probing the psychological side of a literary man in an attempt to disclose its hidden aspects since, it forms a part of human soul in which psychology has interested. In more definite words, this research compares between two psychological studies that were done by each of Al-Aq'qad and An-Nuwaihi on the basis of two complexes. The first is based on the complex of Narcissism based on the love of a man to his self in preference to selves of others; while the second is based on Oedipus complex, which is based on a son's attachment to his mother and his love to possess her. Each of both critics attempted to trace up the complex which he had discovered in the several domains the poet dealt with; such as his passion for wine, homosexuality and, love of women.